Productivity of transhumant Fulani cattle in the inner Niger Delta of Mali - Wagenaar, K.T.; Diallo, A.K.; Sayers, A.R. (International Livestock Centre for Africa, 1986)
Evaluates the productivity of transhumant Fulani cattle in the inner Niger delta of Mali. Summarises the results of the animal productivity study extending from December 1978 - March 1983, which indicated high calf mortality, low reproductive performance and moderate milk production. Identifies constraints limiting the productivity of Sudanese Fulani cattle and suggests interventions aimed at eliminating or ameliorating these constraints